Effect of combined infrared freeze drying and microwave vacuum drying on quality of kale yoghurt melts. Issue 5 (3rd April 2020) - Lao, Yanyan; Zhang, Min; Devahastin, Sakamon; Ye, Yufen
Abstract: Kale yoghurt melts are proposed as a novel snack that can melt in the mouth. However, such melts with thin fresh pulp were difficult to shape when drying at elevated temperature. In order to obtain a desirable shape and high-quality snack, freeze drying (FD), infrared freeze drying (IRFD), and combination of infrared freeze drying and microwave vacuum drying (IRFD-MVD) were attempted. The effects of these drying techniques on the drying time, energy consumption, bulk density, rehydration time, texture, color, chlorophylls, carotenoids and total phenolics contents as well as antioxidant activity and sensory characteristics of the differently dried products were compared. Nuclear magnetic resonance and magnetic resonance image analyses were also conducted to illustrate the state and proportion of water during the IRFD process. Drying time of IRFD was noted to be significantly shorter than that of FD. IRFD-MVD could further save the time as well as energy consumption of drying and, when properly conducted, could maintain the quality of snacks.